THE HISTORY OF THE PERFORMERS AND DEVELOPMENT OF THE RIGHT OF PERFORMERS IN RELATED RIGHTS - Toxirova , Sabina Zoxidjon qizi; Yakubova, I.B. (Educational Research in Universal Sciences, 2023)
In this article, the historical development of the rights of performers, which are the subject of related rights, and the current status of these rights in intellectual property legislation are studied in depth. It also provides an extensive analysis of the challenges faced by performers in the digital age and the ways in which new laws and solutions can be developed to address these challenges.